Investigations on Capacitor Compensation Topologies Effects of Different Inductive Coupling Links Configurations - Norezmi Jamal; Shakir Saat; Y. Yusmarnita; Thoriq Zaid; A. A. M. Isa (Institute of Advanced Engineering and Science, 2015)
This paper presents investigations on capacitor compensation topologies with different inductive coupling links for loosely coupled inductive power transfer (IPT) system. In general, the main constraint of the loosely coupled IPT system is power losses due to the large leakage inductances. Therefore, to overcome the aforementioned problem, in this work, capacitor compensation is proposed to be used by adding an external capacitor to the system. By using this approach, the resonant inductive coupling can be achieved efficiently and hence the efficiency of the system is also increased significantly. This paper analyzes the performance of two different compensation topologies, which are primary series-secondary series (SS) and primary series- secondary parallel (SP) topology. The performance of such topologies is evaluated through the experimental results at 1MHz operating frequency for different types of inductive coupling. From the results, SS topology produces a high power transfer but SP topology gives better efficiency.